Analysis Dynamics of the Market Development of Funds for Investment: on the Example of Major ETF - Serhiienko, Olena; Bril, Mykhailo; Lyashenko, Vyacheslav (My University, 2023)
The sustainable functioning and development of both the economy as whole and individual business entities requires constant investment. Such an investment is possible both with the help of bank lending and on the basis of investment. Each of the approaches has its own advantages and disadvantages. In this paper, we consider investment. Investing comes in various types and forms. One of the types of investment is raising the necessary funds through investment funds. For these purposes, stock market instruments are used. We are considering an ETF fund. We examine the dynamics of the fund's main ETF instruments. For this analysis, we use descriptive statistics and wavelet analysis tools. The paper presents many graphs and charts that allow you to understand the course of the study and evaluate the results.
Keywords: analysis; ETFs investment; dynamics; time series; investment fund; comparative analysis; stock market